What is the Image of Microscale Chemistry Research for Chemistry Teaching in 2013-2023? - Hidayah, Fitria Fatichatul; Indriyanti, Dyah Rini; Madnasri, Sutikno (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
This research aims to reveal the distribution of microscale chemistry research related to publication output, document sources, microscale chemistry publishing countries; countries of correspondent authors on microscale chemistry; number of annual distribution of publication affiliations of microscale chemistry; distribution of microscale chemistry publication sources; the most relevant author in microscale chemistry publications; visualization of microscale chemistry research topics and trends. The method used is a bibliometric study sourced from the scopus.com database. Data were collected through searching publications with the keyword